SANGGAR TUAH SAKATO DALAM INDUSTRI SENI PERTUNJUKAN DI KOTA PADANG :TINJAUAN MANAJEMEN SENI PERTUNJUKAN - Muhammad Trio Idha; Desfiarni Desfiarni; Darmawati Darmawati (FBS Universitas Negeri Padang, 2018)
Abstract This article aimed to describe the Performing Arts Management at Tuah Sakato Studio.This research was qualitative research with descriptive type. This research was conducted at Tuah Sakato Studio in Padang City. The object of the study was the studio of Tuah Sakato in Padang City. The techniques of data collection were interviews, documentation and direct observation in the field. Meanwhile, the analysis of the data used in this study was interpretation technique. The results of the study showed that the management of Tuah Sakato Studio had a planning by making programs that would be carried out and implemented, with preparation of equipment and training. The organizing of the studio had been organized by making the management structure in the form of lines. The organizing also determined the duties and authorities of the board. The movement was done by carrying out the provision of motivation, guidance and mobilizing on the stated goals. Internal supervision was carried out directly or indirectly. In the other hand, external supervision was done with evaluation of activities. Tuah Sakato studio also had a production house consisting of dance, music, Malam Bainai, and babako. Marketing management of Tuah Sakato studio also followed the current development of times. Tuah Sakato studio was already registered in tourism office and cooperated with the office. Of the two management chosen by Sanggar Tuah Sakato, both of them revealed Democracy. Keywords: Sanggar Tuah Sakato, Of The Performing Arts: Performing Arts Management Review